Pengaruh Dompet Digital dan Literasi Keuangan Terhadap Perilaku Konsumtif Mahasiswa di Kota Surakarta - Madhan Abidzar; Mintasih Indriayu; Aniek Hindrayani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine the effect of digital wallets on consumptive behavior, the effect of financial literacy on consumptive behavior, and its simultaneous effect on consumptive behavior in college students in Surakarta City. The research method used was a descriptive quantitative method and data collection techniques used questionnaire. The sampling technique used was non-probability sampling, namely purposive sampling with a sample of 385 undergraduate students in Surakarta. Validity test using product moment and reliability test using Cronbach alpha. The data analysis technique of this research uses multiple linear regression analysis, t test, and F test. The results of this study are obtained: (1) Digital wallets have a significant positive effect on college student consumptive behavior in Surakarta City, digital wallets make it easier for college students to shop anywhere make college students become consumers. (2) Financial literacy has a significant negative effect on the consumptive behavior of college students in Surakarta City, a good understanding of finance makes college students have low consumptive behavior. (3) Digital wallets and financial literacy have a simultaneous effect on the consumptive behavior of college students in Surakarta City.